Pediatric Intensive Care Unit Forensic Cases Study - Muhammad Ihsan Nabil Fadhlurrahman; Citra Manela; Efrida Efrida; Noverika Windasari; Indra Ihsan; Firdawati Firdawati (Arab Journal of Forensic Sciences & Forensic Medicine, 2023)
The pediatric forensic case study encompasses all pediatric cases with potential legal implications, including violence, poisoning, and drowning. While many of these cases receive initial treatment in emergency departments (ED), certain patients are admitted to pediatric intensive care units (PICU) due to poor outcomes. This study aims to determine the profile of pediatric forensic cases in the PICU of a tertiary hospital in Indonesia. This descriptive-observational study used medical records of PICU patients in a tertiary hospital in Indonesia from 2017 to 2023 with a total sampling technique. Among 51 samples obtained, the majority of cases involved violence (78.4%), followed by fracture as the most common injury (29.4%), and equal distribution between chemical substances and pesticides in poisoning cases (5.9% each). Most of the cases in this study occurred unintentionally (93.3%). Remarkably, this study is the first of its kind in Indonesia and holds the potential to inform legal frameworks.